(untitled) (Economics and region, 2018)
It is considered equity as one of the objects of accounting in the state enterprise. Different points of view of scientists regarding the characteristics of equity capital are presented. The basic tasks of accounting of own capital and necessity of creation of funds of budgetary institutions are revealed. It is presented the comparison of accounting of own capital in accounting accounts after reforming in the public sector.